2016
DOI: 10.1159/000446607
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Correlates of Reduced Physical Activity in Idiopathic Pulmonary Fibrosis

Abstract: Background: Little is known about the consequences of idiopathic pulmonary fibrosis (IPF) for physical activity (PA). Objectives: We aimed to investigate levels of PA in IPF and to study associations of PA with lung function, exercise capacity, symptoms, and quality of life. Methods: In stable patients with IPF we measured PA (steps per day, SPD; physical activity level, PAL; minutes of moderate activity, MMA) by accelerometry (SenseWear Armband) for 1 week. We also assessed lung function (forced vital capacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
74
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(85 citation statements)
references
References 23 publications
9
74
1
1
Order By: Relevance
“…This benefit of PR is particularly important, as several studies [8, 15, 21] have shown that exercise intolerance is linked to reduced QoL, dyspnoea, and fatigue, thus frequently creating a persistent vicious circle, as has also been described for other pulmonary diseases [5, 6]. PR can potentially break this circle by increasing exercise capacity and thus enhance physical activity levels in daily life [41]. Moreover, the greatest benefit of PR was seen in the severely exercise-intolerant patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This benefit of PR is particularly important, as several studies [8, 15, 21] have shown that exercise intolerance is linked to reduced QoL, dyspnoea, and fatigue, thus frequently creating a persistent vicious circle, as has also been described for other pulmonary diseases [5, 6]. PR can potentially break this circle by increasing exercise capacity and thus enhance physical activity levels in daily life [41]. Moreover, the greatest benefit of PR was seen in the severely exercise-intolerant patients.…”
Section: Discussionmentioning
confidence: 99%
“…Mutual influences and interlinked physiological training results, such as reduced dyspnoea (MRC), improved physical fitness (6MWD), or reduced fatigue contribute to the improvements in HrQoL after PR. Moreover, 6MWD and SGRQ scores were recently shown to have stronger associations with steps per day, while exercise capacity and QoL measurements were robust predictors of physical activity in patients with sarcoidosis [41]…”
Section: Discussionmentioning
confidence: 99%
“…While one study found physical activity in patients with sarcoidosis and fatigue to be reduced compared to predicted reference values [12], Saligan [11] was not able to show meaningful differences between obese patients with sarcoidosis and sedentary controls. In chronic lung diseases, established clinical parameters such as exercise capacity and lung function, or patient-reported outcomes such as health-related quality of life and generic quality of life, generally show moderate associations with levels of objectively measured physical activity [8][9][10]. However, to the best of our knowledge, those relationships have not yet been investigated in patients with sarcoidosis.…”
Section: Introductionmentioning
confidence: 89%
“…The armband is worn on the upper left arm over the triceps muscle and incorporates amongst other things a triaxial accelerometer that records the average number of steps per day; those are related to key functional characteristics and quality-of-life measures in chronic obstructive pulmonary disease [10,16], asthma [17], idiopathic pulmonary fibrosis [8], and lymphangioleiomyomatosis [9]. We instructed the patients to wear the armband 24 h a day, except for the time spent on personal hygiene.…”
Section: Physical Activitymentioning
confidence: 99%
See 1 more Smart Citation